PERANCANGAN BRAND IDENTITY DESTINASI WISATA BATANG AGAM KOTA PAYAKUMBUH SUMATERA BARAT: DESIGNING THE BRAND IDENTITY OF BATANG AGAM TOURIST DESTINATION PAYAKUMBUH CITY WEST SUMATERA - Akmal; Elda Franzia Jasjfi; Agung Eko Budiwaspada (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Designing The Brand Identity Of Batang Agam Tourist Destination Payakumbuh City West Sumatera. Batang Agam is one of the tourist destinations located in Payakumbuh City, West Sumatra Province. Batang Agam is a destination that has 4 types of tourism, including natural tourism, history, culture, and hydroponic agriculture. This tour has been quite widely known and visited by many local and foreign tourists, but until now Batang Agam tourism has not had a brand identity so that the brand name of this tour tends to change and is inconsistent. In addition, the name of Payakumbuh City is also better known than the name of the tourist itself. Therefore, the research with the title “Designing The Brand Identity Of Batang Agam Tourist Destination Payakumbuh City West Sumatera” aims to produce strategies, concepts, and visual designs of brand identity in order to encourage the creation of a brand image. The data collection methods used are observation, interviews, documentation, and questionnaires. Meanwhile, the method of designing works is carried out using 5 stages of Design Thinking, namely: empathize, define, ideate, prototype and test. The results of this brand identity design have formed strategies, concepts, and visual designs of brand identity in the form of logos, brand guidelines, and the application of identity to media in accordance with brand needs.